¬UJI BEBERAPA KONSENTRASI BIJI PINANG (Areca catechu L.) UNTUK MENGENDALIKAN Helopeltis theivora - Rusli Rustam; Ice S. Hutagalung (DINAMIKA PERTANIAN, 2021)
Cocoa (Theobroma cacao L.) is a plantation commodity that plays an important role in Indonesia’s economic activities and is a potential foreign exchange earner. One of the biggest obstacles in growing cacao in Indonesia is the attack of the cocoa pod-sucking pests (Helopeltis theivora Waterhouse). The aim of this study is to obtain an effective concentration of betel nut to control the fruit-sucking pests (Helopeltis theivora Waterhouse) in cocoa plants in the laboratory. The research was conducted at the Plant Pest Laboratory and Experimental farm, Faculty of Agriculture, Riau University from August to October 2020. The treatment given was the administration of areca nut extract with the following concentrations: P0: 0 g.l-1 water, P1: 20 g.l-1 water, P2: 40 g.l-1 water, P3: 60 g.l-1 water, P4: 80 g.l-1 water, P5: 100 g.l-1 water and 20 experimental units were obtained. The results showed that the application of betel nut had a significant effect in controlling cocoa pod sucking pests (Helopeltis theivora Waterhouse). The application of areca nuts extract at a concentration of 60 g.l-1 of water was an effective concentration in controlling Helopeltis theivora Waterhouse with a mortality of 80% with an initial time of death of 10.50 hours after application and lethal time of 50 which is 33.00 hours after application.